Chemotherapy in advanced pancreatic adenosquamous carcinoma: A retrospective multicenter AGEO study. Issue 9 (3rd January 2023) - Auvray Kuentz, Marie; Hautefeuille, Vincent; de Mestier, Louis; Coutzac, Clélia; Lecomte, Thierry; Nardon, Victor; Artru, Pascal; Turpin, Anthony; Drouillard, Antoine; Malka, David; Tran‐Minh, My‐Linh; Trouilloud, Isabelle; et al.
Abstract: Pancreatic adenosquamous carcinoma (PASC) account for <5% of pancreatic malignancies. The efficacy of modern chemotherapy regimens in patients with advanced PASC is unknown. Patients with advanced PASC from 2008 to 2021 were consecutively included in this retrospective multicenter study. Overall survival (OS) and progression‐free survival (PFS) were evaluated by Kaplan‐Meier method. Ninety‐four PASC from 16 French centers were included (median age, 67.3 years; males, 56.4%; metastatic disease, 85.1%). The first‐line treatment was chemotherapy for 79 patients (84.0%) (37 FOLFIRINOX (FX), 7 Gemcitabine‐nab paclitaxel (GN) and 35 for all other regimen) or best supportive care (BSC) alone for 15 patients (16.0%). No significant difference was observed between FX and GN in terms of PFS ( P = .67) or OS ( P = .5). Modern regimens pooled together (FX and GN) as compared to all others chemotherapy regimens showed an improvement of overall response rate (39.5% and 9.7%, P = .002), PFS (median, 7.8 vs 4.7 months, P = .02) and OS (median, 12.7 vs 9.2 months, P = .35). This large study evaluating first‐line treatment regimens in advanced PASC suggests that modern regimens as FX or GN may be preferable to all other chemotherapy regimens. These results deserve confirmation in prospective studies. Abstract : What's new? Pancreatic adenosquamous carcinoma (PASC) is a rare pancreatic cancer subtype of uncertain histological origin. Owing to its scarcity, little is known about the efficacy of chemotherapy for PASC, particularly for advanced disease. Here, investigation of modern chemotherapy regimens in a large multicenter cohort consisting of patients with advanced PASC suggests that more recent regimens based on 5‐fluorouracil, particularly FOLFIRINOX (FX), as well as regimens based on gemcitabine, namely gemcitabine‐nab paclitaxel (GN), are more effective for advanced PASC compared to more conventional regimens. Notably, overall response rates and survival rates were improved in advanced PASC patients on FX and GN regimens.